PEMBAGIAN BUKU SAKU DAN TABLET TAMBAH DARAH PADA REMAJA PUTRI DI DESA PARENRENG - St. Rosmanely; Suci Rahmadani; Eva Arista; Adhelin Tiku Rombedatu; Chelnilo Pasudi; Amada Amealia Putri; Yuana Wira Dwi Satya Ilham Putra (Gapenas Publisher, 2023)
Anemia is a condition in which the levels of hemoglobin and red blood cells are lower than normal and are still a public health problem in Indonesia. Adolescent girls are a group prone to anemia, because women's need for iron is three times higher than that of men. Supplementation of Blood Supplement Tablets (TTD) in young women is one of the Indonesian government's efforts to meet iron intake. Providing iron supplements at the right dose can prevent anemia which can affect academic achievement in young women, as well as increase body iron stores to prepare young women to become anemia-free mothers (during pregnancy). The target of this program is the young women of Parenreng Village. This activity was carried out starting from the distribution of Pocket Books and Blood Supplement Tablets as well as an explanation regarding the contents of the Pocket Books. This aims to increase the knowledge and understanding of young women about the dangers of anemia and recommendations for taking iron tablets. The distribution of pocket books and blood supplement tablets was carried out at the Parenreng Village Office Hall, Segeri District, Pangkajene and Islands Regencies. 19 pocket books distributed and 200 blood supplement tablets (TTD) given to young women.